Analysis of the Cultural Dimensions of Indonesian People on Purchase Decisions: A Case Study of Karen's Diner Restaurant in Indonesia - Atikah Amaliadanti; Niken Febrina Ernungtyas; Lukita Wijaya (Publikasi Indonesia, 2024)
This study uses a constructivist paradigm and a qualitative approach to analyse six elements of Hofstede's Cultural Dimensions Theory. Data analysis was taken from four viral tweets collected with the keyword Karen's Diner on Twitter from December 15 to 22, 2022. The study results show that six elements of the Cultural Dimensions Theory are inherent in Indonesian consumers, so they oppose the concept of service presented by Karen's Diner. The element of power distance applies where most Indonesian people have been instilled with the idea that